Aksesibilitas dan Pemanfaatan Aplikasi “ Jogja Smart Service” untuk Mewujudkan Good Governance - Novia Wahyu Indriyani; Rosalia Prismarini Nurdiarti; M. Nastain (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The city of Yogyakarta is one of the developing smart city developments. Smart city is an urban service that is carried out by utilizing the role of information technology. This technology-based public service is realized through the “Jogja Smart Service” (JSS) application. From jss.jogjakota.go.id data, currently the number of active users of the